Pulmonary abnormalities in mice with paracoccidioidomycosis : a sequential study comparing high resolution computed tomography and pathologic findings (2010)
ABSTRACT: Background: Human paracoccidioidomycosis (PCM) is an endemic fungal disease of pulmonary origin. Follow-up of pulmonary lesions by image studies in an experimental model of PCM has not been previously attempted. This study focuses on defining patterns, topography and intensity of lung lesions in experimentally infected PCM mice by means of a comparative analysis between High Resolution Computed Tomography (HRCT) and histopathologic parameters. Methodology: Male BALB/c mice were intranasally inoculated with 36106 Paracoccidioides brasiliensis (Pb) conidia (n = 50) or PBS (n = 50). HRCT was done every four weeks to determine pulmonary lesions, quantify lung density, reconstruct and quantify lung air structure. Lungs were also analyzed by histopathology and histomorphometry. Results: Three different patterns of lesions were evidenced by HRCT and histopathology, as follows: nodular-diffuse, confluent and pseudo-tumoral. The lesions were mainly located around the hilus and affected more frequently the left lung. At the 4th week post-challenge HRCT showed that 80% of the Pb-infected mice had peri-bronchial consolidations associated with a significant increase in upper lung density when compared with controls, (2263625 vs. 2422610 HU, p,0.001). After the 8th and 12th weeks, consolidation had progressed involving also the middle regions. Histopathology revealed that consolidation as assessed by HRCT was equivalent histologically to a confluent granulomatous reaction, while nodules corresponded to individual compact granulomas. At the 16th week of infection, confluent granulomas formed pseudotumoral masses that obstructed large bronchi. Discrete focal fibrosis was visible gradually around granulomas, but this finding was only evident by histopathology. Conclusions/Significance: This study demonstrated that conventional HRCT is a useful tool for evaluation and quantification of pulmonary damage occurring in experimental mouse PCM. The experimental design used decreases the need to sacrifice a large number of animals, and serves to monitor treatment efficacy by means of a more rational approach to the study of human lung disease.